KONTEN MARKETING PADA AKUN INSTAGRAM@LAZIS SABILILLAHCOM DALAM PENGGUNAA BAHASA GAUL - Imam Hasan Albasri; Rokhyanto Rokhyanto; Endang Sumarti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
The focus of the research and how to obtain data from this type of research is called interpretive descriptive research. Of course, the document approach used in this research is to find out that the data is the result of the author's creativity using the media of language that is perpetuated for the sake of evidence. Research related to internet-intagram accounts that are applied in the form of results of information from the Sabilillahcom Mosque is more appropriate and appropriate if it is called a type of description-type documentation research. The data sources include: items contained in the form of the use of sentences and detailed contextual descriptions of the intentions expressed in the Instagram account. The data sources in this study are Indonesian novel texts, including: (1) to gain a broad understanding of the Instagram account @lazissabilillahcom, (2) to find out the detailed description of sentences (discourse) on the use of contemporary language in marketing content on the Instagram account @ lazissabilillah com. The data collection technique in this study is the analysis of documentary studies (documentary sudy). Documentary study is a data collection technique by collecting and analyzing written documents. The data collected is data that has a relationship with the analysis that is being studied. From this paper it can be concluded that: The use of modern language is part of familiarity for social contacts with colleagues to make them more intimate. Especially the relationships every day. In general, each informant knows the contemporary language very differently, both in place and in the community.